2015
DOI: 10.1590/1678-4162-8054
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of autogenous bone graft for the treatment of a radius-ulna nonunion in an amputee dog

Abstract: Universidade Estadual Paulista -Unesp-Jaboticabal  Jaboticabal, SP ABSTRACTFracture nonunions represent important complications in orthopedic surgeries. Nonunion repairs or bone defects are surgically challenging. Our aim was to describe a nonunion case, which was repaired with rapid bone recovery. An 8-month-old male mixed breed dog that has been previously operated was presented to the Veterinary Medical Teaching Hospital of São Paulo State University, with a right radiusulna nonunion and an amputated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…If grafts are infected, it may be necessary to perform an amputation of the affected limb in the worst case. In a study that reported the use of autologous cortical bone graft in the radius of a dog, fusion of the bone was observed postoperatively in two months, and reconstruction was observed in six months 5. In the present study, progress in the fusion of bone, seen radiographically as an enhanced opacity at the boundary of the host bone and the graft, was observed three months after surgery in case 1 and six months after surgery in case 2.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…If grafts are infected, it may be necessary to perform an amputation of the affected limb in the worst case. In a study that reported the use of autologous cortical bone graft in the radius of a dog, fusion of the bone was observed postoperatively in two months, and reconstruction was observed in six months 5. In the present study, progress in the fusion of bone, seen radiographically as an enhanced opacity at the boundary of the host bone and the graft, was observed three months after surgery in case 1 and six months after surgery in case 2.…”
Section: Discussionsupporting
confidence: 62%
“…In a study that reported the use of autologous cortical bone graft in the radius of a dog, fusion of the bone was observed postoperatively in two months, and reconstruction was observed in six months. 5 In the present study, progress in the fusion of bone, seen radiographically as an enhanced opacity at the boundary of the host bone and the graft, was observed three months after surgery in case 1 and six months after surgery in case 2. In addition, the collapse of the reconstructed diaphysis or loosening of the implant did not occur, which corroborates the role of the graft in providing mechanical support.…”
Section: Discussionsupporting
confidence: 57%
“…Fractures with large bone defects and bone non-union are a serious challenge for both human and veterinary orthopaedics (Minto et al, 2015). The main factors with adverse effect on fracture healing are the impaired blood supply in the fracture line area, presence of foreign bodies, necrotic tissues, bone sequestra, infection, maladaptation of bone fragments and inadequate osteosynthesis technique (Piermattei et al, 2006).…”
Section: Discussionmentioning
confidence: 99%